A rare case of subcutaneous emphysema in a young and healthy patient with parainfluenza virus 3 pneumonia - Yahia Yaseen Akeely; Saleh Alesa; Hassan Gafar Hassan; Sultan Almarzouqi; Mohamad Ziad Alchammat; Omar Elghor; Shabana Begum Patel; Emad Hamdi Shaat (Respirology Case Reports, 2024)
Abstract An 18‐year‐old healthy male complained of a 7‐day history of fever, cough, and sore throat, along with a three‐day history of left facial swelling. The x‐rays revealed subcutaneous emphysema in the chest, neck, face, and mediastinum region (Pneumomediastinum). Furthermore, an area of infiltration was visible, indicating pneumonia. Therefore, we immediately started him on intravenous antibiotics. We then moved the patient to an isolation room, considering pulmonary tuberculosis as one of the differential diagnoses. However, the Acid Fast Bacilli (AFB), Mycobacterium Tuberculosis Bacteria‐Polymerase Chain Reaction (MTB PCR), and sputum for gram stain and culture were all negative. On the other hand, the test for parainfluenza virus 3 was positive. The patient was observed with a daily chest x‐ray to monitor the progress of pneumonia and subcutaneous emphysema. Fortunately, the subcutaneous emphysema was significantly reduced on a daily basis until it was completely resolved before discharge home.